Measuring Green Marketing Strategy for Resort Spa in Bali - Rr. Astrid Adiyanti Prawitasari; Ida Bagus Raka Suardana (Universitas Pendidikan Nasional, 2019)
ABSTRACT According to the expert, the spa industry is still growing and can be used as green washing. Therefore, it is important for the spa industry to also poised to offer adequate solutions and lead the way on how we can achieve sustainable well being within protecting the world. Fairmont Sanur The Spa, as the winner of Best Leading Spa Resort 2017/2018 by Bali Tourism Award realize the increase interest of customer for ‘something green’ also impact their business. The customers sincere awareness about environment make them realize that they might have to run things differently from now on, starting with checking their green marketing strategy due to up until now they only focus on the regular marketing. The purpose of this study is to develop a green marketing strategy for the green spa industry which is exemplified by Fairmont Sanur The Spa. This research used qualitative method that is constructive with literature review and management interview as the premier data source. The result of this study is finding that Fairmont Sanur The Spa needs to focus more on their promotion in terms of strategy, therefore a strategy for promotional activity is made. This research contributes to the resort spa business where they need to focus on their green movement as a whole to ensure the quality of the products and services offered. Further studies can be can be conducted to find standardization on green spa, therefore even though they have been doing all the green marketing, they do not have a certificate that can assure their green business.